Program Penguatan Keberanian Berpendapat Siswa melalui Media One Paper Plane, One Question, One Brave Opinion dalam Pembelajaran Bahasa Inggris - Ikhya'ul Farokh; Sudarwanti Sudarwanti; Miftahul Huda (Education and Community Service Journal (EduServe), 2026)
This community service program was conducted at SMA Al Karimi Tebuwung as an effort to address students’ low confidence in expressing their opinions orally during English language learning. Although students had previously studied the topic of Expressions of Asking and Giving Opinion, their verbal participation and self-confidence remained relatively low. The program introduced an innovative and simple learning medium called One Paper Plane, One Question, One Brave Opinion, which integrates the principles of the Love-Based Curriculum through equal opportunities to speak, a psychologically safe learning environment, and positive reinforcement for every student’s opinion. The program employed a participatory approach involving the partner teacher in the planning, implementation, and evaluation stages. The participants consisted of 30 tenth-grade students (Class X-A). Evaluation was carried out through speaking tests, observations of verbal participation, and self-confidence questionnaires. The results showed an increase in the average speaking score from 65.75 to 81.25, an improvement in verbal participation from 40% to 93%, and a rise in self-confidence scores from 2.7 to 4.2 on a five-point scale. In addition to benefiting students, the program also enhanced teachers’ capacity to implement participatory learning strategies that can be easily adapted to other learning materials. These findings indicate that a simple learning medium based on active participation can effectively foster students’ confidence in expressing their opinions while supporting the sustainability of instructional innovation in partner schools.